Studies and simulations on the flight trajectories of spinning table tennis ball via high-speed camera vision tracking system - Wang, P.; Zhang, Q.; Jin, Y.; Ru, F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
When a table tennis ball is hit by a racket, the ball spins and undergoes a complex trajectory in the air. In this article, a model of a spinning ball is proposed for simulating and predicting the ball flight trajectory including the topspin, backspin, rightward spin, leftward spin, and combined spin. The actual trajectory and rotational motion of a flying ball are captured by three high-speed cameras and then reconstructed using a modified vision tracking algorithm. For the purpose of model validation, the simulated trajectory is compared to the reconstructed trajectory, resulting in a deviation of only 2.42%. Such high modeling accuracy makes this proposed method an ideal tool for developing the virtual vision systems emulating the games that can be used to train table tennis players efficiently.